Richard Strauss und die Sächsische Staatskapelle: Tagungsband - Mende, Wolfgang; Ottenberg, Hans-Günter (Georg Olms Verlag, 2019)
Salome, Elektra, and Der Rosenkavalier all started their triumphant international careers in Dresden, where they received highly acclaimed premieres. In all, nine stage works as well as other works by Richard Strauss were baptised here, and every time the composer himself conducted the orchestra that he loved. In the context of the stated theme, the 17 essays published here engage with aspects of composition and its circumstances as well as those of interpretation and equally of the presentation of source material. The special character of this richly-illustrated volume comes from its combination of the perspectives of practitioners and historians.